Drought characteristics and their impacts on vegetation net primary productivity in the subtropical China - Ye, Qing; Feng, Wenzhong; Jiao, Gengying; Deng, Wenping (Frontiers in Ecology and Evolution, 2023)
Drought is one of the main factors restricting limiting the productivity of forestsforest productivity, it has an important impact on theand thus greatly affects carbon sink capacity of forests. In this study, Here we first chose the two commonly used drought indices includingthe standardized precipitation evapotranspiration index (SPEI) and self-calibrating Palmer drought severity index (scPDSI), to reflect and evaluate analyze the spatio-temporal characteristics patterns of drought in the evergreen broad-leaved forests of the southern in the subtropical China. Then, Based on the NDVI and meteorological data, we used tthe verified validated CASA (Carnegie-Amer-Stanford Approach) model was applied to estimate the forest net primary productivity (NPP) in the study area and then quantified the responses of NPP to droughtand further quantify the contributions of drought events and their characteristics on forest NPP. The results showed that, both SPEI-and scPDSI-based drought reduced the NPP, with androught events during 2000-2015 have resulted in a mean decline of forest NPP by average magnitude of 7.2%. NPP was reduced the most by mModerate or severe drought instead of extreme drought events reduced NPP more significantly than the extremely severe drought events; NPP was reduced the least by abnormally dry conditions. In addition, there was a 1-2 years of lagging in the NPP responses to drought for the study forests; the lagging, and the lagging time varied among the land typeswith forest types. Our study suggests that the forest managers and local governments should pay more attention to the places with moderate and severe drought events, and take measures to avoid NPP decline within the 2 years after drought. Our study also provides data support for further identifying contribution of drought to ecosystem carbon fluxes in the subtropical China.